2015
DOI: 10.1016/j.frl.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Credit rationing for Portuguese SMEs

Abstract: Available online xxxx JEL classification: C31 E44 E51 G21 a b s t r a c tThis study examines the importance of credit demand and credit supply-related factors in explaining the evolution of credit granted to Portuguese SMEs. The results suggest that the interest rate is a strong driver of SMEs' demand for bank loans, as well as their internal financing capacity. On the other hand, credit supply mostly depends on the firms' ability to generate cash-flows and reimburse their debt, and on the amount of collateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Beck et al (2006) used the World Business Environment Survey (WBES) and showed that a high interest rate is the most important financing obstacle for SMEs among 12 examined financing obstacles. Farinha and Felix (2015) found that banks with lower interest rates received more loan applications as compared to banks with higher interest rates in Portugal. A study also showed that higher interest rate is one of the most significant factors for SMEs causing loan default as the higher price of loans increases the debt burden for SMEs (Chaibi and Ftiti, 2015).…”
Section: H5: Availability Of Collateral Increases Access To Financementioning
confidence: 99%
“…Beck et al (2006) used the World Business Environment Survey (WBES) and showed that a high interest rate is the most important financing obstacle for SMEs among 12 examined financing obstacles. Farinha and Felix (2015) found that banks with lower interest rates received more loan applications as compared to banks with higher interest rates in Portugal. A study also showed that higher interest rate is one of the most significant factors for SMEs causing loan default as the higher price of loans increases the debt burden for SMEs (Chaibi and Ftiti, 2015).…”
Section: H5: Availability Of Collateral Increases Access To Financementioning
confidence: 99%
“…Casey et al [5] use Euro area firm-level data since the recent financial crisis, as opposed to credit financing, and smaller, self-rationing borrowers are more likely to apply for grant finance. Farinha and Félix [6] examine the importance of credit demand and credit-supply-related factors in explaining the evolution of credit granted to Portuguese SMEs. e results suggest that credit supply mostly depends on the firms' ability to generate cash flows and reimburse their debt, and on the amount of collateral.…”
Section: Introductionmentioning
confidence: 99%
“…The interest rate associated with commercial loans is also the main hurdle for entrepreneurial SMEs, and entrepreneurial SMEs are not willing to take advances from banks. Farinha and Félix (2015) established that banks with lower interest rates had received more requests for loans as compared to high interest rates for SMEs. Studies disclosed that high rate of interest discourages SMEs to get credits from banks and other financial institution because the cost of advances are high and has a negative impact upon SMEs performance (Hern andez-C anovas and Koëter-Kant, 2011).…”
Section: Introductionmentioning
confidence: 99%